Effects of high pressure processing on safety and quality of durian (Durio zibethinus L.) paste and pulp - Tan, Peh Fen (2018)
High pressure processing (HPP) or high hydrostatic pressure (HHP) is a method of applying high pressure in the preservation of food products. In this study, HPP with the pressures of 300, 400, 500 and 600 MPa combined with time of 3, 5, 10 and 15 min were studied. The effect of HPP on the physicochemical (proximate composition, colour, total soluble solids, pH and titratable acidity), microbiological (total plate count, coliforms, yeasts and moulds, and psychrophilic bacterial counts), enzymatic (reduction of polygalacturonase and pectin methyl esterase activities) properties, and sensory evaluation was carried out in durian paste and pulp. It was observed that HP-treated durian paste and pulp showed no significant changes (p > 0.05) in terms of their proximate composition, colour, total soluble solid, pH, titratable acidity and sensory attributes. In addition, the reduction of microbial counts to below detection level (< 20 CFU/g) in both durian paste and pulp were observed at treatment pressures of above 500 MPa and 400 MPa, respectively. Meanwhile, pressure as a treatment factor was found to exhibit a significant effect (p <0.05) in reducing both polygalacturonase and pectin methyl esterase activities for both durian paste and pulp. This finding showed that HPP is a promising method in preserving durian. After several HPP parameters were evaluated, optimum parameters of 600 MPa for 5 min and 500 MPa for 5 min were selected for durian paste and pulp, respectively, with microbial safety being set as the primary deciding factor. The selected optimum parameters were applied onto nylon-packed durian paste, nylon-packed and skin film-packed durian pulps. Then, the treated durian paste and pulp were stored at -18°C and subjected to a 56-day shelf life study. During the storage period, it was observed that the total soluble solids, pH, titratable acidity and colour of HP-treated durian paste and pulp did not show any significant changes (p > 0.05).Meanwhile, the microbial counts of HP-treated samples were shown to be lower than those of the untreated samples and did not show any significant changes throughout the storage period. Furthermore, the enzymatic activities of durian paste and pulp were lower than those of the untreated samples during the storage period. In this study, it was also showed that there was little difference between durian pulp packaged using nylon and skin film packaging, suggesting the minimal effect of packaging types on the durian pulp. Overall, HPP showed promising result in maintaining the overall qualities of durian paste and pulp. At the same time, the effective reduction of microbial and enzymatic activities pointed to the possibilities of shelf life extension with minimal quality deterioration in durian paste and pulp.